Improving the management of acutely agitated patients in the emergency department through implementation of Project BETA (Best Practices in the Evaluation and Treatment of Agitation) - Lynn P. Roppolo; David W. Morris; Fuad Khan; Rohini Downs; Jeffery Metzger; Tiffany Carder; Ambrose H. Wong; Michael P. Wilson (Journal of the American College of Emergency Physicians Open, 2020)
Abstract Agitated patients presenting to the emergency department (ED) can escalate to aggressive and violent behaviors with the potential for injury to themselves, ED staff, and others. Agitation is a nonspecific symptom that may be caused by or result in a life‐threatening condition. Project BETA (Best Practices in the Evaluation and Treatment of Agitation) is a compilation of the best evidence and consensus recommendations developed by emergency medicine and psychiatry experts in behavioral emergencies to improve our approach to the acutely agitated patient. These recommendations focus on verbal de‐escalation as a first‐line treatment for agitation; pharmacotherapy that treats the most likely etiology of the agitation; appropriate psychiatric evaluation and treatment of associated medical conditions; and minimization of physical restraint/seclusion. Implementation of Project BETA in the ED can improve our ability to manage a patient's agitation and reduce the number of physical assaults on ED staff. This article summarizes the BETA guidelines and recent supporting literature for managing the acutely agitated patient in the ED followed by a discussion of how a large county hospital integrated these recommendations into daily practice.